Great battles of World War II - Macdonald, John 1945- (Chartwell Books, 2003)
A stunning new look at the most spectacular campaigns of World War II, this book uses incredible computer graphics to recreate every detail of the most significant battles and strategies. Topography and troop strength, illustrations and maps of actions carried out are presented with the latest technology down to the smallest detail.